Paradigm shift in finance: The transformation of the theory from perfect to imperfect capital markets using the example of company valuation - Dietmar Ernst; Werner Gleißner (Journal of Risk and Financial Management, 2022)
In the capital market and financing theory, we are currently observing major upheavals. For decades, the neoclassical paradigm has dominated in science and practice. Triggered by economic and political crises, transformations, the COVID-19 pandemic, and political instabilities, a paradigm shift is currently occurring in finance. This paradigm shift leads to models and theories that can explain imperfections in capital markets and provide decision support for managers. The aim of this article is to analyse the paradigm shift and to demonstrate it using an example of business valuation theory. We draw on the insights of the philosopher Thomas Samuel Kuhn. He vividly explains the paradigm shift in science in his major work "The Structure of Scientific Revolutions". A paradigm shift in science always encounters resistance. The reasons for this include the strong neoclassical school in finance and the dependence on research funds. Funders expect the use of established methods and the simplicity and dissemination of the models that have prevailed so far. On the other hand, the neoclassical models are unsuitable to explain the transformation processes on financial markets. This fact has been empirically proven. We show a variety of arguments that speak clearly about this paradigm shift. Their importance clearly outweighs the reasons to continue subscribing to the old paradigm. Accordingly, new theories and models have been developed to better explain the changes in the markets. With the simulation-based business valuation, an approach has been developed that considers different degrees of market imperfections. The simulation-based valuation can also depict the special case of the neoclassical paradigm, so that all market constellations can be covered.
Keywords: 650; capital market theory; CAPM; company valuation; Monte Carlo simulation; paradigm shift; simulation-based valuation